Diagnosis of the Sugar-Energy Sector in Paraná State and Assessment of its Potential for Producing Electricity and Biomethane from Biogas - Penteado, Maurício Cabral; Furtado, Andreia Cristina (International Journal of Advanced Engineering Research and Science, 2022)
The sugar-energy sector is one of the main economic activities in Brazil and has a high availability of residues with the potential for biogas production. In this sense, the present study sought to analyze the characteristics of the sugarcane processing plants and to define a theoretical plant with the average characteristics for the state of Paraná, with the aim of identifying the biogas production potential of this unit and to evaluate the monetization strategy that presents the best results. The analysis performed shows that the state has 23 units in operation that have an installed capacity to process up to 246,530 tons of sugarcane per day; the biogas production potential of the theoretical plant would produce over 21,127 MWh.year-1 of electric energy or 6,302,463 Nm³.year-1 of biomethane. When analyzing the different monetization methods of biogas, the self-consumption of biomethane associated with the commercialization of the surplus portion presented a better financial performance (R16.1 million.year-1) when compared to the exclusive sale of biomethane (R12.6 million.year-1) or electricity (R7.3 million.year-1).